HISTOARCHITECTURE OF EPIDERMIS OF SNAKE - Narkhede, H P; Suryawanshi, V P; Ladukar, O N; Suryawanshi, R D; Ladukar, Neeta; Shankhpal , V D (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The epidermis of snake showed three distinct layers, β cell, mesos and α cell layers. β cell layer and α cell layer located externally and internally respectively. The mesos layer located between β and α cell layer showed bilayer structure and consisted of 2-3 layers of nucleated cells. The basal cells of mesos layer are large may be indicative of renewal phase in snake.
Keywords: Histoarchitecture; snake; epidermis